Comprehensive utilization method of sub-biberschreiberite produced in aluminum electrolyte lithium extraction process

CN118026208BActive Publication Date: 2026-10-09DO FLUORIDE CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410196654.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-22
Publication Date
2026-10-09
Estimated Expiration
2044-02-22

AI Technical Summary

Technical Problem

目前,针对铝电解质提锂工艺副产亚冰晶石的综合利用工艺未见相关报道,基于此,本专利申请就是针对这种新产的粗亚冰晶石进行提纯及综合利用

Benefits of technology

1)目前市面上还未出现对高纯亚冰晶石的研究,本发明技术方案,能够对不纯的亚冰晶石进行纯化利用,最终产物可以转化为氟化氢钠(可进一步热分解为氟化钠和氢氟酸售卖),也可以进一步加工成为高纯的亚冰晶石新型材料、或高纯的高分子冰晶石,为以后的材料科学研究提供实物基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present application relates to a kind of aluminum electrolyte lithium extraction process by-product cryolite comprehensive utilization method: preparation mass concentration 20%~42%, temperature is between 20 ℃~30 ℃ alkali liquor;By-product cryolite is added to the above-mentioned alkali liquor and is stirred, and carbon impurities are floated by stirring;After flotation, temperature is kept at 85 ℃~95 ℃ by stirring and heating, and 2~3h is reacted, solid-liquid separation is obtained, and solid A and liquid A are obtained;Solid A is mainly NaF, and liquid A is mainly NaAl (OH) 4;Under the condition of temperature 40 ℃~60 ℃ and stirring, solid A is mixed with concentration 10%~25% hydrofluoric acid and reacts 0.5h~2h, after reaction, solid-liquid separation is carried out, and solid is washed to neutral with water, and solid B and liquid B are obtained, wherein solid B is NaHF2, and solid B is further reacted with liquid A and is converted into cryolite or cryolite.The present application not only can change waste into treasure, obtain high-purity sodium hydrogen fluoride, cryolite or cryolite product, purity is more than 99%, but also can create economic benefits to aluminum electrolyte lithium extraction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sub-crystal purification technology, and more specifically, it is a comprehensive utilization method developed for sub-crystal, a byproduct of the lithium extraction process from aluminum electrolytes. Background Technology

[0002] Sub-crystal, also known as cone cryolite, has the molecular formula Na5Al3F. 14 It belongs to the tetragonal crystal system and is a white, fine-grained crystal. The main difference between sub-crystal and cryolite (molecular formula Na3AlF6) lies in their shape and structure. Sub-crystal is a single-crystal structure; it is not made up of atomic arrangement but rather of many small hexagonal blocks, usually with irregular shapes. Cryolite is composed of hexagonal single-crystal atoms arranged in a very precise and regular shape, with each hexagon having exactly the same side length. This difference in shape and structure results in significant differences in the physical properties of sub-crystal and cryolite. For example, sub-crystal is much less hard than cryolite, while cryolite has a more uniform refractive index.

[0003] With the rapid development of the new energy industry, the demand for lithium carbonate has increased, and the recycling of lithium resources has become a hot research topic. Therefore, research on lithium extraction processes using aluminum electrolytes has emerged in recent years. Due to the characteristics of the aluminum electrolyte source process, the slag after lithium extraction inevitably contains impurities such as carbon, aluminum, silicon, and calcium, with fluorine, aluminum, and sodium remaining the main elements. After treatment with an aluminum-containing leaching agent, aluminum electrolytes yield a byproduct mainly composed of cryolite. The chemical composition of this byproduct is shown in Table 1.

[0004] Table 1. Chemical composition analysis of the byproduct subcryolite (wt / %) As shown in Table 1, the silicon and calcium content of the byproduct subcrystal is far higher than the quality standards required by GB / T 4291-2017 CM-1, and the carbon content is around 5%. The presence of carbon inevitably causes the subcrystal to appear gray. Diffraction analysis revealed that this type of subcrystal also contains alumina. Therefore, this byproduct has little industrial value. If impurities in the subcrystal are effectively removed, not only can the waste be turned into a valuable resource, but the cost of the aluminum electrolyte lithium extraction process can also be reduced. Currently, there are no reports on the comprehensive utilization process of subcrystal byproducts of the aluminum electrolyte lithium extraction process. Based on this, this patent application focuses on the purification and comprehensive utilization of this newly produced crude subcrystal. Summary of the Invention

[0005] The purpose of this invention is to overcome the defects of existing technologies and provide a comprehensive utilization method for sub-cryolite, a byproduct of the aluminum electrolyte lithium extraction process. By using the method of this invention to process the sub-cryolite, the impurities in the sub-cryolite can be made to meet the national standards for ordinary cryolite. The final product can be converted into sodium bifluoride, or further processed into high-purity sub-cryolite new materials or high-purity polymer cryolite. This not only effectively maximizes resource utilization but also creates economic benefits for the aluminum electrolyte lithium extraction process.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for the comprehensive utilization of sub-crystal, a byproduct of lithium extraction from aluminum electrolytes, involves first mixing the crude sub-crystal with an alkaline solution, then using upper foam flotation to remove carbon impurities. Following flotation, a high-temperature reaction is carried out to ensure that both the sub-crystal and alumina react fully with the alkaline solution (primarily to remove alumina). After solid-liquid separation, solid A and liquid A are obtained. Solid A is then reacted with hydrofluoric acid to remove silicon and calcium, followed by solid-liquid separation to obtain solid B and liquid B. Solid B and liquid A are mixed, and the pH is adjusted to generate solid C. By adjusting the parameters during the formation of solid C, it is possible to obtain either high-purity sub-crystal or high-purity cryolite. The specific steps of this method are as follows: 1) Prepare an alkaline solution with a mass concentration of 20%~42% and a temperature between 20℃ and 30℃; 2) Slowly add the by-product subcrystal to the above alkaline solution and stir at low speed. This process is exothermic and bubbles appear on the upper layer. The bubbles contain black carbon. By stirring at low speed, the carbon impurities are floated out. 3) After flotation, the mixture is stirred and heated to maintain the temperature of the slurry at 85℃~95℃ for 2~3 hours, allowing both cryolite and alumina to fully react with the alkaline solution. After the reaction, solid and liquid are separated to obtain solid A and liquid A. Solid A mainly consists of crude NaF. Based on the detection results of solid A, it is inferred that liquid A mainly consists of NaAl(OH)4. The reactions involved in this step are as follows: Na5Al3F 14 + 12NaOH = 3NaAl(OH)4+ 14NaF ↓ 4) Under conditions of 40℃~60℃ and stirring (stirring speed controlled at 250rpm~450rpm), solid A is mixed with hydrofluoric acid with a mass concentration of 10%~25% and reacted for 0.5h~2h. After the reaction, the solid and liquid are separated, and the solid is washed with water until neutral to obtain solid B and liquid B, wherein solid B is NaHF2; the main reactions involved in this step are as follows: NaF + HF = NaHF2↓

[0007] The comprehensive utilization method of subcrystalite, a by-product of the above-mentioned aluminum electrolyte lithium extraction process, also includes step 5), which involves mixing solid B and liquid A and heating them to 50°C~80°C, introducing CO2 gas to make the pH of the mixed system between 5 and 9, stirring for 0.5-1 h, separating the solid and liquid, and drying them to obtain cryolite or subcrystalite.

[0008] Specifically, in step 1), the alkaline solution is an aqueous solution of sodium hydroxide.

[0009] Furthermore, in step 2), the solid-liquid mass ratio of the by-product subcryolite to the alkaline solution is 1:3~5. The low-speed stirring speed is 50rpm~100rpm.

[0010] Furthermore, in step 3), after flotation is completed, the stirring speed is controlled at 200 rpm to 500 rpm. Specifically, in step 4), the solid-liquid mass ratio of solid A to hydrofluoric acid with a concentration of 10%~25% is 1:2~5. In this step, silicon and calcium impurities in the solid are dissolved and transferred to the liquid. To obtain better impurity removal effect, a small amount of hydrochloric acid, sulfuric acid, or nitric acid can be added to the reaction in step 4), preferably a small amount of concentrated hydrochloric acid, concentrated sulfuric acid, or concentrated nitric acid; the molar ratio of HCl, H2SO4, or HNO3 to HF is preferably 0.02-0.05:1.

[0011] Furthermore, in step 5), the amount of solid B used determines the type of product. When the molar ratio of NaHF2 to NaAl(OH)4 is 2.8~3:2, the product is cryolite, and the solution is mainly sodium carbonate; when the molar ratio of NaHF2 to NaAl(OH)4 is 2.1~2.5, the product is sub-cryolite, and the solution is mainly sodium carbonate.

[0012] Furthermore, in step 5), the drying temperature is 80℃~120℃.

[0013] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) Currently, there is no research on high-purity subcrystal on the market. The technical solution of this invention can purify and utilize impure subcrystal. The final product can be converted into sodium hydrogen fluoride (which can be further thermally decomposed into sodium fluoride and hydrofluoric acid for sale), or it can be further processed into high-purity subcrystal new materials or high-purity polymer cryolite, providing a physical basis for future materials science research.

[0014] 2) The present invention is used to modify the by-product sub-cryolite. The process is simple and can not only turn waste into treasure and effectively maximize resource utilization to obtain high-purity sodium bifluoride, sub-cryolite or cryolite products with a purity of over 99%, but also create economic benefits for the lithium extraction process of aluminum electrolyte. Attached Figure Description

[0015] Figure 1 The image shows the XRD pattern of slag A obtained in Example 1; the image shows that slag A is NaF; indicating that the crude subcryolite reacted under strong alkaline conditions to produce solid NaF. Figure 2 The image shows the XRD pattern of solid B obtained in Example 1; the figure shows that solid B is NaHF2, indicating that NaF was converted into NaHF2 during the hydrofluoric acid purification process. Figure 3 The image shows the XRD pattern of the solid product obtained in Example 2; the image shows that the solid product is subcrystal; indicating that solid B and filtrate A produced pure subcrystal through a carbonization process. Figure 4 The image shows the XRD pattern of the solid product obtained in Example 4; the image shows that the solid product is cryolite, indicating that solid B and filtrate A produced pure cryolite through a carbonization process. Detailed Implementation

[0016] The technical solution of the present invention will be further described in detail below with reference to the embodiments, but the scope of protection of the present invention is not limited thereto.

[0017] In the following embodiments, all raw materials used are commercially available commodities or can be prepared using conventional methods in the art. For example, commercially available 98wt% concentrated sulfuric acid and commercially available 36-38wt% concentrated hydrochloric acid are used. The crude cryolite, a byproduct of the aluminum electrolyte lithium extraction process, is sourced from Do-Fluoride Chemicals Co., Ltd., and its elemental composition and proportions are shown in Table 2 below.

[0018] Table 2 Chemical composition analysis of by-product subcryolite (wt / %) In the following embodiments, the process steps not mentioned in detail can be carried out using conventional techniques in the art, as they are not the innovation of this application, and therefore will not be described in detail.

[0019] Example 1 A method for the comprehensive utilization of sub-cryolite, a byproduct of lithium extraction from aluminum electrolytes, specifically includes the following steps: 1) Prepare 400g of a 30% sodium hydroxide solution, stirring until the solution temperature drops to 25℃. 2) Then, slowly add 100g of by-product crude cryolite to the above alkaline solution and stir at a speed of 80 rpm to float out 6g of wet carbon. 3) The slurry temperature was then controlled at 90℃, and the reaction was carried out at a stirring speed of 250 rpm for 3 hours. After the reaction was completed, the mixture was filtered to obtain filtrate A and residue A, which is crude sodium fluoride. The XRD patterns of these residues are shown in the attached figure. Figure 1 ; 4) Weigh 300g of 20% hydrofluoric acid, stir at 300rpm, heat to 50℃, add 8.8g of concentrated sulfuric acid (the molar ratio of H2SO4 to HF is approximately 0.03:1) and 112g of residue A to the hydrofluoric acid, and stir at 50℃ for 1 hour. After the reaction is complete, filter to obtain 220g of wet residue, and after drying, obtain 157.3g of solid B. Its XRD pattern is shown in the appendix. Figure 2 . Figure 2 The results showed that solid B was NaHF2 with a purity of 99.6%.

[0020] Example 2 A method for the comprehensive utilization of sub-cryolite, a byproduct of lithium extraction from aluminum electrolytes, specifically includes the following steps: 1) to 4) are the same as in Example 1; 5) Weigh 95g of solid B and mix it with the above filtrate A. Heat the mixture to 60℃, introduce CO2 gas to lower the pH of the system to 9, and then maintain this pH value while stirring continuously for 0.5h. Filter to obtain a wet paste, dry at 100℃ to obtain 99.5g of white solid product, sub-crystal, with a purity of 99.67%. See attached XRD pattern. Figure 3 .

[0021] Example 3 A method for the comprehensive utilization of sub-cryolite, a byproduct of lithium extraction from aluminum electrolytes, specifically includes the following steps: 1) Prepare 400g of a 30% sodium hydroxide solution, stirring until the solution temperature drops to 25℃. 2) Then, slowly add 100g of by-product crude cryolite to the above alkaline solution and stir at a speed of 80 rpm to float out 6g of wet carbon. 3) Then, the slurry temperature was controlled at 90℃ and the stirring speed was 250rpm for 3 hours. After the reaction was completed, the mixture was filtered to obtain filtrate A and residue A. 4) Weigh 300g of 20% hydrofluoric acid, stir at 300rpm, and heat to 50℃. Add 9g of concentrated hydrochloric acid (HCl to HF molar ratio approximately 0.03:1) and 110.7g of residue A to the hydrofluoric acid. Maintain stirring at 50℃ for 1 hour. After the reaction is complete, filter to obtain 222g of wet residue. After drying, obtain 155.4g of solid B. The XRD result of solid B shows that it is NaHF2 with a purity of 99.7%.

[0022] Example 4 A method for the comprehensive utilization of sub-cryolite, a byproduct of lithium extraction from aluminum electrolytes, specifically includes the following steps: 1) to 4) are the same as in Example 3; 5) Weigh 121g of solid B and mix it with the above filtrate A. Heat the mixture to 60℃, introduce CO2 gas to lower the pH of the system to 8, and then maintain this pH value while stirring continuously for 1 hour. Filter to obtain a wet paste, dry at 90℃ to obtain 136.0g of white solid cryolite with a purity of 99.61%. See attached XRD pattern. Figure 4 .

Claims

1. A method for the comprehensive utilization of subcryolite, a byproduct of lithium extraction from aluminum electrolytes, characterized in that, Includes the following steps: 1) Prepare an alkaline solution with a mass concentration of 20%~42% and a temperature between 20℃ and 30℃; 2) Add the by-product subcrystal to the above alkaline solution and stir. This process is exothermic and the upper layer bubbles. The foam contains black carbon. The carbon impurities are removed by stirring and flotation. 3) After flotation, stir and heat to maintain the temperature at 85℃~95℃ for 2~3 hours. After the reaction, separate the solid and liquid to obtain solid A and liquid A; solid A is mainly NaF, and liquid A mainly contains NaAl(OH)4. 4) Under the conditions of temperature 40℃~60℃ and stirring, solid A is mixed with hydrofluoric acid with a concentration of 10%~25% and reacted for 0.5h~2h. After the reaction is completed, the solid and liquid are separated. The solid is washed with water until neutral to obtain solid B and liquid B, wherein solid B is NaHF2. 5) Mix solid B and liquid A and heat to 50℃~80℃. Introduce CO2 gas to make the pH of the mixture between 5 and 9. Stir for 0.5-1h, separate the solid and liquid, and dry to obtain cryolite or sub-cryolite.

2. The method for comprehensive utilization of sub-cryolite, a byproduct of the lithium extraction process using aluminum electrolyte as described in claim 1, is characterized in that... In step 1), the alkaline solution is an aqueous solution of sodium hydroxide.

3. The method for comprehensive utilization of sub-cryolite, a byproduct of the aluminum electrolyte lithium extraction process as described in claim 1, is characterized in that... In step 2), the solid-liquid mass ratio of the by-product subcryolite to the alkaline solution is 1:3~5.

4. The method for comprehensive utilization of subcryolite, a byproduct of the aluminum electrolyte lithium extraction process as described in claim 1, is characterized in that... In step 2), the stirring speed is 50 rpm to 100 rpm.

5. The method for comprehensive utilization of sub-cryolite, a byproduct of the aluminum electrolyte lithium extraction process as described in claim 1, is characterized in that, In step 3), after flotation is completed, the stirring speed is controlled at 200 rpm to 500 rpm.

6. The method for comprehensive utilization of subcryolite, a byproduct of the lithium extraction process using aluminum electrolyte as described in claim 1, is characterized in that... In step 4), the solid-liquid mass ratio of solid A to hydrofluoric acid with a concentration of 10% to 25% is 1:2 to 5.

7. The method for comprehensive utilization of sub-cryolite, a byproduct of the lithium extraction process using aluminum electrolyte as described in claim 1, is characterized in that... In step 5), when the molar ratio of NaHF2 in solid B to NaAl(OH)4 in liquid A is 2.8~3:2, the product is cryolite, and the solution after solid-liquid separation mainly contains sodium carbonate; when the molar ratio of NaHF2 in solid B to NaAl(OH)4 in liquid A is 2.1~2.5, the product is sub-cryolite, and the solution after solid-liquid separation mainly contains sodium carbonate.

8. The method for comprehensive utilization of sub-cryolite, a byproduct of the lithium extraction process using aluminum electrolyte as described in claim 1, is characterized in that... In step 5), the drying temperature is 80℃~120℃.

9. The method for comprehensive utilization of sub-cryolite, a byproduct of the aluminum electrolyte lithium extraction process as described in claim 5, is characterized in that, Step 4) Add appropriate amounts of hydrochloric acid, sulfuric acid or nitric acid to the reaction; the molar ratio of hydrochloric acid, sulfuric acid or nitric acid to hydrofluoric acid is 0.02-0.05:1.